Unveiling the temporally contingent role of codification in alliance success - Heimeriks, Koen H.; Bingham, Christopher B.; Laamanen, Tomi (Strategic Management Journal, 2015)
While prior research highlights the importance of codifying alliance experience to achieve alliance success, it is unclear whether codification is equally useful in the different phases of an alliance. Based on a sample of 192 technology firms that report on over 3,400 strategic alliances, we find that in the partner selection and termination phases, reliance on codified knowledge is useful. However, in the partner management phase, reliance on codified knowledge is less beneficial and can be even negatively related to performance. Our findings have implications for the tension between flexibility and efficiency and the relationship between structure and performance . Copyright © 2013 John Wiley & Sons, Ltd.